False negative bronchial artery caliber on multi-detector computed tomography in predicting outcome of bronchial artery embolization in patient with haemoptysis - Soo, Tze Hui; Tharek, Anas; Ibrahim, Idris; Zakaria, Mohd Hazeman; Mohd Yaakob, Mohd Naim; Kamis, Mohammad Fandi Al-Khafiz; Abdul Malik, Mawaddah (Longe Medikal, 2022)
Bronchial artery embolization was first performed in 1973 by Remy et al with widespread acceptance since then. Multi-detector computed tomography (MDCT) CT angiography (CTA) is currently the gold standard imaging modality used to identify the site and cause of bleeding in patient presented with haemoptysis. Bronchial artery anatomies and precise location can be obtained by scrutinizing CTA prior to interventional procedures. CTA has the advantage of not only can preclude the need of digital subtraction angiography (DSA) in inappropriate cases, but also can shorten the intervention procedure timing. We present a case of false negative bronchial artery caliber seen on MDCT which was abnormal in DSA.